REDESAIN STRUKTUR GEDUNG KAMPUS STFK LEDALERO 3 LANTAI MENGGUNAKAN KONSTRUKSI BAJA - Ignasius Anwal Mo'an Hure; Firnimus Konstantinus Bhara; Sandy I. Yansiku (Program Studi Teknik Sipil, 2021)
Steel structures are metal structures made of structural steel components that are connected to carry loads and provide full and even stiffness and strength. The STFK Ledalero Campus Building is a multi-story building whose main structure uses a reinforced concrete structure and will be re-planned to use steel construction. This campus building is located in earthquake area 5 and will be used as offices and classrooms, so the planning for this building must meet excellent safety criteria by applicable regulations. In planning this steel structure, current standard regulations are used, namely SNI 1729:2020 which refers to the LRFD method with several load combinations by the provisions in SNI-1726-2019, SNI 1727:2020, and PPPURG 1987. Structural analysis uses the help of SAP 2000 v.14, to determine the magnitude of the moment, shear force, and axial force values in the upper structure of the building, namely the beams and columns, against the working loads. The results of the analysis of the redesign of the 3-story STFK Ledalero campus building using BJ 37 showed that the steel profile dimensions for the Main Column used WF 400x400x13x21, the Terrace Column used WF 350x350x12x19, the main beam used WF 450x200x9x14 and for the child beam used WF 350x175x7x11, the roof main beam used WF 294x20 0x8x12, Block Roof rafters use WF 244.175.7.11, Terrace Beams use WF 244.175.7.11, the conclusion is that the structure is safe against moments, shear forces and axial forces.